OPTIMALISASI PERSEDIAAN BAHAN BAKAR MINYAK PADA PT. MINAS JAYA ABADI DI KABUPATEN BERAU (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2017)
The purpose of this study is to determine the optimization of fuel stock at PT. Minas Jaya Abadi in Berau District. Analyzer used in this research is Economic Order Quantity (EOQ) and Reorder Point (ROP). Based on the result of the research, it can be seen that the most optimal order of fuel oil (economic) based on EOQ (Economic Order Quantity) method is 542,827 liters for each order with order frequency 5 times in 1 year. The reorder point is at 113.340 liters, meaning that the ordering of fuel oil should be made at the time the remaining inventory amount of fuel is 113,340 liters. The goal is that when the fuel oil order comes, the company does not use fuel oil from the safety stock set by the company of 37,780 liters. The optimal ordering frequency using EOQ method is 5 times with total order cost of Rp.35.512.500 so that there is savings / efficiency of the ordering cost of Rp.49.717.500, it can be concluded to accept the proposed hypothesis that fuel supply control oil at PT. Minas Jaya Abadi in Berau Regency is not yet optimal.